Penerapan Prinsip Ta‘zir terhadap Pelaku Tindak Pidana Ringan dalam Putusan Nomor 156/Pid.B/2020/PN.Pre - Ben Albar; Johandi Fadli; Suci Lestari; Azzahra Salsabilla; Mytha Bianka; Susilawati Susilawati (Journal of Sharia and Legal Science, 2025)
Minor crimes are simple violations of the law that still impact social order. This study aims to analyze the application of the ta'zir principle to perpetrators of minor crimes in Decision Number 156/Pid.B/2020/PN.Pre and examine its relevance to Islamic values ​​of justice. The research method used is qualitative with a normative juridical approach, based on an analysis of court decisions, Islamic criminal law literature, and related legal sources. The results show that judges impose educational and proportional sentences, taking into account the perpetrator's social and economic conditions. This approach aligns with the ta'zir principle, which emphasizes moral development, public welfare, and substantive justice. Thus, the application of the ta'zir principle in this decision reflects the harmony between Islamic law and national law in upholding humanistic justice.